Chitosan-Based Polyion Multilayer Coating on NPK Fertilizer as Controlled Released Fertilizer - Yuni Kusumastuti; Alit Istiani; Rochmadi; Chandra Wahyu Purnomo (Advances in Materials Science and Engineering)
Low efficiency of conventional fertilizer (quick release fertilizer) application in agricultural sectors has caused environmental pollution and health problems. A method to overcome the drawback of the conventional fertilizer is by controlled release fertilizer (CRF) preparation. CRF is expected to be able to fulfil the nutrient demand of targeted plants. The objective of this research is to prepare CRF by coating NPK fertilizer with multilayer chitosan-polyanion using alginate, pectin, and sodium tripolyphosphate (TPP). In addition, the effect of the layer arrangement modification of material on the rate of nitrogen release was also studied. The mechanical strength of coated fertilizer was analysed by compressive stress test and the properties of the fertilizer coating was observed by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The nitrogen release study shows that multilayer of chitosan-alginate (CA)5, chitosan-pectin (CP)5, and chitosan-TPP (CT)5 as coating material was able to increase the compressive stress and decrease the nitrogen release of coated fertilizer. These results are supported by the FTIR analysis which exhibits the formation of ionic interaction between amine group of chitosan and carboxyl group of alginate in chitosan-alginate (CA)5 layer, carboxyl group of pectin in chitosan-pectin (CP)5 layer, and phosphate of TPP in chitosan-TPP (CT)5 layer. On the other hand, the modification of the arrangement of chitosan-alginate layers showed that the fertilizer with the alternating layer arrangement (CA)5 was able to optimally increase the compressive strength. The mathematical model for the nitrogen release of coated fertilizer is also prepared and simulated with the MATLAB software. The simulation results showed that the nitrogen release of coated fertilizer followed the proposed diffusion mechanism. The obtained diffusivity coefficient value in the layer of chitosan-alginate (CA)5 is 2.0933 × 10−6 cm2/s, 2.5606 × 10−6 cm2/s in chitosan-TPP (CT)5 layer, and 3.7256 × 10−6 cm2/s in chitosan-pectin (CP)5 layer.